2005
DOI: 10.1021/ja0508929
|View full text |Cite
|
Sign up to set email alerts
|

Long-Range Ordered Thin Films of Block Copolymers Prepared by Zone-Casting and Their Thermal Conversion into Ordered Nanostructured Carbon

Abstract: Large-scale alignment of lamellae in thin films of diblock copolymers containing polyacrylonitrile and poly(n-butyl acrylate) was achieved by casting copolymer solution on a silicon substrate moved away at a constant speed from the casting nozzle (zone-casting). Grazing incidence small-angle X-ray scattering revealed that the lamellae, which were perpendicular to the substrate, were also aligned over macroscopic scale in the direction perpendicular to the casting direction. Such long-range ordered block copoly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
218
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(226 citation statements)
references
References 15 publications
7
218
1
Order By: Relevance
“…Techniques for aligning block copolymer include solvent evaporation fields [46], physical epitaxy/graphoepitaxy [90], chemical epitaxy [4], optical (holographic) radiation [91], droplet pinning [92], shear forces [93], nanoimprint lithography [94], e-beam lithography [95], zone annealing [96] and casting [97]. We concentrate in this section on graphoepitaxy (including nanoimprint lithography) and chemical pre-patterning as these techniques represent the most practical methods for device integration.…”
Section: Block Copolymer Thin Filmsmentioning
confidence: 99%
“…Techniques for aligning block copolymer include solvent evaporation fields [46], physical epitaxy/graphoepitaxy [90], chemical epitaxy [4], optical (holographic) radiation [91], droplet pinning [92], shear forces [93], nanoimprint lithography [94], e-beam lithography [95], zone annealing [96] and casting [97]. We concentrate in this section on graphoepitaxy (including nanoimprint lithography) and chemical pre-patterning as these techniques represent the most practical methods for device integration.…”
Section: Block Copolymer Thin Filmsmentioning
confidence: 99%
“…In the second category, uniform solvent annealing [19] can increase BCP grain size to a few microns without imposing a preferential direction to the pattern; by creating a moving gradient in solvent concentration, "zone-casting" from solution can produce macroscopically-aligned specimens. [20] Similarly, uniform thermal annealing [21,22] increases the grain size without imposing a preferential direction, but the grain size grows only as the 1 ⁄4 power of annealing time; the effect of a moving temperature gradient on a block copolymer thin film has not been reported previously.Hashimoto et al [23] showed that sweeping a strong temperature gradient through a bulk specimen of a lamellar BCP, such that the material is heated above its order-disorder transition temperature, can produce strong alignment; as the material cools in the gradient, ordered lamellae grow from the disordered phase, with the lamellar planes aligned normal to the direction of the moving gradient. Though directional solidification has not been reported for neat BCP thin films, directional crystallization of a small-molecule solvent from a BCP solution has been reported by Thomas and co-workers; [24,25] crystallization of the solvent concentrates the BCP and drives it to order, similar to what zone-casting [20] achieves through solvent evaporation.…”
mentioning
confidence: 98%
“…[20] Similarly, uniform thermal annealing [21,22] increases the grain size without imposing a preferential direction, but the grain size grows only as the 1 ⁄4 power of annealing time; the effect of a moving temperature gradient on a block copolymer thin film has not been reported previously.…”
mentioning
confidence: 98%
“…[9][10][11] Especially, the controlled structuring of large surface areas of many square millimeters remains challenging. Preparation routes based on diblock copolymers require the use of external fields and several special chemical steps to end up with highly aligned polymer nanochannels: [12][13][14][15] With the help of the external field, the local lamellar order is expanded in a stripe-like pattern and a secondary chemical treatment is necessary to remove one block, yielding the nanochannels. Preparation routes based on optical interference result in large scale and extremely perfect surface gratings, 16 but the special type of equipment required does not match the idea of a simple process.…”
mentioning
confidence: 99%